The Meaning of Media Texts and Materiality in Medieval Scandinavia - Horn, Anna Catharina; Johansson, Karl G. (Modes of Modification, 2021)
This book addresses various aspects of materiality and mediality in the manuscript culture of Scandinavia represented in epigraphic writing with runes, the introduction of Roman script and the earliest period of print. The materiality, in stone, lead amulets, parchment and paper, and how it formed part of the literate culture in the Middle Ages is highlighted.